2018
DOI: 10.5056/jnm17035
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect ofMelissa officinalisL. in Visceral Hypersensitivity in Rat Using 2 Models of Acid-induced Colitis and Stress-induced Irritable Bowel Syndrome: A Possible Role of Nitric Oxide Pathway

Abstract: Background/AimsThe aim of present study is to estimate the effects of Melissa officinalis L. (MO) on visceral hypersensitivity (VH), defecation pattern and biochemical factors in 2 experimental models of irritable bowel syndrome (IBS) and the possible role of nitric oxide.MethodsTwo individual models of IBS were induced in male Wistar-albino rats. In the acetic acid model, the animals were exposed to rectal distension and abdominal withdrawal reflex, and the defecation patterns were determined. In the restrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Regarding antioxidant enzymes, decreased superoxide dismutase, catalase, and glutathione peroxidase activities were described for IBS patients, as compared to the healthy controls [32, 33]. These observations were also confirmed by IBS animal model studies of oxidative stress implication description as significantly increased lipid peroxidation and reduced antioxidant defense in intestinal tissues of several IBS rat models [5, 34].…”
Section: Introductionmentioning
confidence: 67%
“…Regarding antioxidant enzymes, decreased superoxide dismutase, catalase, and glutathione peroxidase activities were described for IBS patients, as compared to the healthy controls [32, 33]. These observations were also confirmed by IBS animal model studies of oxidative stress implication description as significantly increased lipid peroxidation and reduced antioxidant defense in intestinal tissues of several IBS rat models [5, 34].…”
Section: Introductionmentioning
confidence: 67%
“…They were orally administered the test sample, depending on their group, for 4 weeks. To develop an IBS model where IBS was induced by chronic restraint stress, all groups were immobilized using plastic restrainers, allowing a close fit for 1 h daily during the 4 weeks of treatment ( Figure 1 ) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…They were orally administered the test sample, depending on their group, for 4 weeks. To develop an IBS model where IBS was induced by chronic restraint stress, all groups were immobilized using plastic restrainers, allowing a close fit for 1 h daily during the 4 weeks of treatment (Figure 1) [28]. During the study period, the bodyweight of the rats was checked daily, and stool consistency and serum corticosterone levels were assessed on the last day of every week.…”
Section: Rats and Study Designmentioning
confidence: 99%
“…Regarding the oxidative stress implications in IBS, we previously described several correlations between the IBS pathological mechanisms and oxidative stress occurrence [ 20 ] and also recent reports showed that both signalling impairments and oxidative balance changes occur in some gastrointestinal and neurological disorders [ 21 , 22 ]. In this way, the oxidative changes were described in both IBS patients [ 23 25 ] and animal models [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%